Real-time implementation of SVPWM-sensorless vector control of induction motor using an extended Kalman filter - Mustapha Bendjima; Abdeldjebar Hazzab; Mansour Bechar; Medjdoub Khessam; Miloud Rezkallah; Ambrish Chandra; Hussein Ibrahim (Institute of Advanced Engineering and Science, 2023)
In this research paper, space vector pulse width modulation (SVPWM)-sensorless vector control of an induction motor using an extended Kalman filter is presented. The aim of the proposed sensorless control method is to design, implement, and test a sensorless vector control scheme by simulation and experimental implementation. An extended Kalman filter (EKF) simultaneously estimates the rotor speed, the stator stationary axis components (iαs, iβs), and the rotor fluxes (jαs, jβs). The measured stator voltages and currents are employed as inputs for a recursive filter. Simulation results under various operating conditions validate the performances and effectiveness of the proposed observer. The experimental system consists of a host computer with two subsystems: console (SC) and master (SM). The SM subsystem converts to real-time C code, and this code is uploaded into OP5600 real time digital simulation (RTDS) for real-time execution. The obtained experimental results prove that the EKF speed observer can replace the speed or position sensor. This has the benefits of reducing the drive system’s size and overall cost as well as high system reliability.